2022
DOI: 10.1038/s41596-022-00750-2
|View full text |Cite
|
Sign up to set email alerts
|

HT-smFISH: a cost-effective and flexible workflow for high-throughput single-molecule RNA imaging

Abstract: In HT-smFISH, multiple RNA probes are generated by parallel in vitro transcription from a large pool of unlabeled oligonucleotides. This reduces costs per targeted RNA compared to many smFISH methods, is easily scalable, and flexible in design.PROPOSED TWEET: HT-smFISH is a cost effective and flexible method for high-throughput single molecule RNA probe synthesis and imaging. @AdhamSafieddine @IGMM_Montpel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In each cell, both approaches detect similar patterns for the number and spatial locations of mRNA within the nuclei (Fig 5B-G). For our particular choice of image processing algorithm ([66, 76, 32]) and intensity threshold for spot detection (see Methods) and a two-pixel (x,y,z) Euclidean distance threshold for co-localization detection, after analyzing 155 cells in steady-state conditions, we found that 34.8% of mRNA spots (12,231 out of 35,151 total) were detected in both channels (e.g., spots denoted by white triangles in Fig 5A). However, many spots (27.7%, 9,750 spots) are detected only using smiFISH (e.g., those denoted with magenta triangles) and 37.5% (13,170 spots) are only detected using the MS2-MCP labels (e.g., green triangles).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each cell, both approaches detect similar patterns for the number and spatial locations of mRNA within the nuclei (Fig 5B-G). For our particular choice of image processing algorithm ([66, 76, 32]) and intensity threshold for spot detection (see Methods) and a two-pixel (x,y,z) Euclidean distance threshold for co-localization detection, after analyzing 155 cells in steady-state conditions, we found that 34.8% of mRNA spots (12,231 out of 35,151 total) were detected in both channels (e.g., spots denoted by white triangles in Fig 5A). However, many spots (27.7%, 9,750 spots) are detected only using smiFISH (e.g., those denoted with magenta triangles) and 37.5% (13,170 spots) are only detected using the MS2-MCP labels (e.g., green triangles).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we employed Python to implement an image processing pipeline comprising three steps: cell segmentation, spot detection, and data management (as previously described in [66]). Nuclear segmentation on the DAPI channel (405nm) was carried out using Cellpose ([76]) with a 70-pixel diameter as an input parameter.…”
Section: Methodsmentioning
confidence: 99%
“…26 Hence, implementing multiwell readouts in smFRET experiments should lend itself a powerful approach to probe many different conditions in a fully automated manner within a single continuous experiment under controlled conditions. Fluorescence microscopy experiments for large-scale screening, for example, of single-molecule fluorescence in situ hybridization (smFISH), RNA interference or organoids, have been automated already in many applications based on 96-well or larger multiwell plates [27][28][29] . However, this powerful platform has not yet been transferred to a format suitable for applications in smFRET experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Several FISH imaging methods have been developed, such as single-molecule FISH (smFISH), , branched DNA (bDNA) FISH, , and hybrid chain reaction (HCR). , These methods share the goal of amplifying signals by recruiting multiple fluorescent molecules to a specific RNA molecule. For example, early methods like smFISH employed 10–50 fluorescent molecules tethered to individual mRNA molecules of a target gene, resulting in dim signals due to limited fluorescent molecule binding.…”
Section: Introductionmentioning
confidence: 99%
“…As a spatial transcriptomic technique, multiplex FISH profiles transcript molecules at the single-cell level, allowing exploration of tissue organization's molecular signatures. 3−6 Several FISH imaging methods have been developed, such as single-molecule FISH (smFISH), 7,8 branched DNA (bDNA) FISH, 5,9 and hybrid chain reaction (HCR). 10,11 These methods share the goal of amplifying signals by recruiting multiple fluorescent molecules to a specific RNA molecule.…”
Section: Introductionmentioning
confidence: 99%